(untitled) (Texas Journal of Medical Science, 2022)
Сcomputed tomography (CT) is widely used in the diagnosis of degenerative pathology of the lumbar spine, but the relationship between clinical manifestations of lumbar stenosis and its anatomical prerequisites has not been sufficiently studied to date. The objective: to determine the significance of the morphometric parameters of lumbar stenosis according to CT scans and to establish their relationship with the prevailing symptoms of the disease. Material and methods. Seventy-five consecutive patients with clinically significant lumbar stenosis who underwent CT scan before surgery were enrolled in this study. The average values of thirteen different morphometric parameters were calculated at LIII–SI levels of the intervertebral discs and of the pedicels in the axial and sagittal views. The possibility of classification of clinical observations and the correlation of morphometric parameters with the clinical forms of lumbar stenosis were investigated using discriminant and logistic regression analysis. Results CT scan with high probability allocates patients with predominant symptoms of neurogenic claudication or bilateral radiculopathy. The most significant morphometric predictors of this clinical group are the depth of the lateral recesses and the cross-sectional area of the spinal canal. Conclusion CT scan significantly expands the informative value of magnetic resonance imaging and can be used in planning the decompressive stage of the surgery intervention in patients with lumbar spinal canal stenosis.